Pengaruh Penerapan E-Commerce Terhadap Strategi Pemasaran Umkm Deli Serdang Di Era Digital Tahun 2024 - Manalu, Pius Deski; Putra, Aidil; Pakpahan, Evalina (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2024)
This study aims to analyze the effect of e-commerce implementation on the marketing strategy of Micro, Small, and Medium Enterprises (MSMEs) in Deli Serdang in the digital era in 2024. The use of digital technology, especially e-commerce, has significantly changed the business landscape, requiring MSMEs to adapt in order to maintain competitiveness. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to MSME actors in Deli Serdang who have adopted e-commerce. Data analysis was carried out using descriptive and inferential statistics, including validity, reliability tests, and simple linear regression to determine the effect of the independent variable (e-commerce implementation) on the dependent variable (MSME marketing strategy). The results of the study are expected to provide a comprehensive picture of the contribution of e-commerce in strengthening MSME marketing strategies, as well as its implications for the development of MSMEs in Deli Serdang. These findings are expected to be a reference for local governments, MSME associations, and MSME actors themselves in formulating more effective policies and strategies in the future.